Strategies for a web-based mathematics course - Semião, Paulo (2014)
In this paper we will describe the main aspects and strategies for the implementation, development, and deployment of an on-line mathematics course. We also point out some key issues of the infrastructure needed for creating and operating this kind of system. Although this is a huge subject and has many aspects to cover we sketch some guidelines that will help anyone in the implementation of a project with these features. The main topics for such a course will range from basic to advance and are given through a gradually process.